2013
DOI: 10.1128/jcm.01467-13
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Aspiration Culture for Preoperative Diagnosis of Infection in Total Hip or Knee Arthroplasty

Abstract: dThis meta-analysis evaluated preoperative aspiration culture for diagnosing prosthetic joint infection (PJI) in total hip arthroplasty (THA) and total knee arthroplasty (TKA). The pooled sensitivity and specificity were 0.72 (95% confidence interval, 0.65 to 0.78) and 0.95 (0.93 to 0.97), respectively. Subgroup analyses revealed nonsignificant worse diagnostic performance for THA than for TKA (sensitivity, 0.70 versus 0.78; specificity, 0.94 versus 0.96). Preoperative aspiration culture has moderate to high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 51 publications
3
37
1
2
Order By: Relevance
“…This may be due to a number of factors, including a difference in the load of microorganisms, administration of antimicrobials before aspiration, and the infecting pathogen. Finally, a recent meta-analysis of 34 studies including 3,332 patients found a pooled sensitivity of 72% and a specificity of 95% for synovial fluid culture (293). Subgroup analysis was unrevealing but did not examine the method of culture.…”
Section: Synovial Fluid Analysismentioning
confidence: 99%
“…This may be due to a number of factors, including a difference in the load of microorganisms, administration of antimicrobials before aspiration, and the infecting pathogen. Finally, a recent meta-analysis of 34 studies including 3,332 patients found a pooled sensitivity of 72% and a specificity of 95% for synovial fluid culture (293). Subgroup analysis was unrevealing but did not examine the method of culture.…”
Section: Synovial Fluid Analysismentioning
confidence: 99%
“…We did consider Ն3 intraoperative biopsy samples sufficient when tissue samples of the same surgical site were compared before and after the administration of antimicrobial prophylaxis, since a false-negative culture due to sampling error is less likely in this case. The risk of bias was considered high for the reference test when patients did not serve as their own control and culture yield was compared only with that of a control group (31). Since variations in bacterial inoculum are not expected in chronic PJI, the risk of bias regarding the interval between the collection of preoperative synovial fluid and intraoperative samples (flow and timing) was neglected.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol used in the present meta-analysis was conducted as described in our previous studies (6,7,29) and based on recommendations in the methodological guidelines for conducting systematic reviews studying diagnostic accuracy (30) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (31).…”
Section: Methodsmentioning
confidence: 99%
“…GS is also commonly used in the diagnosis of PJI, particularly in developing countries, as a result of its low cost, rapid turnaround time and ease of use; however, its value remains controversial due to conflicting results on the effectiveness of GS in the diagnosis of PJI (5,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The present meta-analysis was therefore performed as one of a series of meta-analyses (6,7,29) in order to evaluate the detection validity of GS for the diagnosis of PJI and to provide evidence-based advice to clinicians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation